Diplomatic & consular directory. (Manila Diplomatic Post Publishing Corporation, 1995)
May serve as a basic guide for diplomats, government officials, businessmen, lawyers, protocol officers, corporate secretaries, students and teachers of foreign service. The directory presents the diplomats and consuls listed alphabetically by country including information on the embassy's' address, country's national day, and staff. the directory also features an ambassadorial and consular resume section, directory of the Department of Foreign Affairs, Directory of Philippine Embassy and Consulates, directory of anniversaries, foundations, independence days, and national days arranged by month, and a section on the Vienna Convention and on Diplomatic relations and on Consular Relations.
It contains useful information on the diplomats and other international civil servants of different countries and world bodies represented in the Philippines including Filipino diplomats based in other countries. This publication can help individuals, private organizations and government agencies in need of the services of embassies, consulates, international organizations, diplomats and students of diplomacy.
Keywords: Diplomatic and consular service -- Philippines -- Directories